EXPERIENCES OF SOCIAL EXCLUSION AMONG YOUNG DEAF ADULTS INFLUENCING THEIR BELIEFS AND PERCEPTIONS OF HIV/AIDS - Ismail, Amanda; Henderson, Neil (Social Work/Maatskaplike Werk, 2014)
This paper reports on a Master’s study whose aim was to capture the beliefs and perceptions of young deaf adults about HIV/AIDS in the Cape Metropole and surrounding areas. The study utilised the explorative, contextual and qualitative descriptive study design. Purposive sampling was implemented and data were collected through focus groups and in-depth interviews. Data were analysed using content analysis. Ethical considerations were adhered to. The main findings of the study indicate that numerous myths and misperceptions about HIV/AIDS prevail among deaf people. This paper advocates for policymakers to include deaf people, particularly sign language users, in HIV-prevention programmes.